Standardization of parenteral nutrition – a review of protocol development in a tertiary neonatal setup - Kessani, Vikram K.; Mehwish, Syeda; Rahim, Anum; Bham, Asma A.; Ali, Syed R. (International Journal Of Community Medicine And Public Health, 2021)
Infants, who are either born preterm or with a weakened gastrointestinal tract, cannot tolerate feeds immediately after their birth normally through enteral route. This is where parenteral nutrition (PN) comes in, which employs ways to maintain the child’s nutrition through ways other than enteral route. PN can be of individualized type, one which is customized for each neonate, while the other is a standardized PN, which has some empirical components absolutely necessary for the infants. Both kinds help in maintaining the optimum nutritive requirements of the infants. However, there are some differences in their effects, which can be noteworthy.